Examining the impact of structural breaks on long memory of stock returns: evidence from Bombay stock exchange of India long memory / Anju Bala and Kapil Gupta - Bala, Anju; Gupta, Kapil (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2020)
This study examines the presence of long memory of Stock Returns in India with reference to structural breaks. The study used the Hurst Exponent in Rescaled Range Analysis as proposed by Lo (1991) to measure the presence of long memory on daily stock returns of the Bombay Stock Exchange Indices from January 2000 to December 2017. The analysis indicates that all indices show long memory effects. It is also evident that all indices exhibit long memory effect in the pre and post subprime crisis period. These findings are consistent with Bhattacharya and Bhattacharya (2018), Jha et al.(2018), Goudarzi (2010) and Lillo and Farmer (2004).